การออกแบบและสร้างเครื่องเจียระไนพลอยแบบอัตโนมัติ - สมจินต์ ธนานันทศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This thesis describes the design and development of an automatic faceting machine. The faceting machine has 6 motion axes. Four axes are necessary for the grinding process and need to be controlled precisely. The motions of these four axes are controlled by a microcomputer control. The other two axes are the grinding wheels rotation and the grinding wheel table turning. There are 3 grinding wheels installed on a table used for rough grinding, semi-polish grinding, and polishing. Cubic Zirconia is used as the testing gemstone. The hardness of the cubic zirconia is 8.5 Mohs. The test consists of two batches of 5.5 mm. and 8 mm. in diameter. The results of the experiment, which certified by the Gem and Jewelry Institute of Thailand (GIT), are in the level of good for 5.5 mm. and fair for 8 mm. The proportional ratio is a criterion in the measurement. But if we consider only the size uniformity in each batch, the output will be considered in the acceptable range.